Race relations in the Waimarino, 1880-1911 : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in History at Massey University - Voelkerling, Rex Herbert (Massey University, 1970)
This thesis makes an examination of Maori-Pakeha relations in the Waimarino area of the King Country in the belief that all too often Maori history is approached on a national scale and viewed within a framework of national trends and Parliamentary Acts. Through the explorations of the dynamics of a bi-racial community it is hoped a regional corrective may be made to former national interpretations. A local study possesses the advantage of getting back to the 'grass-roots'. History is reduced to its very common denominator, the individual in a small community. From a point of 'culture contact' the emphasis in this thesis is placed on the years leading up to the new century, these initial years being crucial in determining the future of race-relations in the Waimarino. Briefly, it was not a series of Land Acts so much as particular comments and actions on the local level which influenced both Maori and European attitudes. These comments and actions have been investigated up to 1911 with one exception: the liquor question has been pursued to the early 1920's, it being very difficult to formulate any sort of a conclusion prior to this period in time.
Keywords: Ngāti Tūwharetoa; New Zealand people; History; Race relations; Waimarino County